История Удмуртии, XX век: учебник для 9-го класса общеобразовательных учреждений / Т. Е. Никулина - Никулина Татьяна Евгеньевна (Удмуртия, 2011)
Экземпляры: (20170913) / Инвентарный номер: 49729 / Цена: 238.00 / Авт.знак: Н 65 / ББК: 63.3(2Рос=Удм) я7